Analysis of the Effectiveness of Internal Audit Sales of Receivables at PT. Raflesindo Surya Mandiri Bengkulu - Deni Saputra; Ahmad Soleh; Rinto Noviantoro (Journal of Indonesian Management, 2021)
The purpose of this study was to determine the extent to which the Effectiveness Analysis of the Internal Audit of Receivables at PT. Raflesindo Surya Mandiri Bengkulu. The analytical method used in this research is descriptive analysis method. Answer Percentage obtained through scoring. The results of respondents' answers can say that the implementation of internal audit on the occurrence of all indicators is effective, and the effectiveness of internal audit on activities at PT Raflesindo Surya Mandiri is very important, the percentage is between 76- 100%.